CLASS SHIFTS OF NOUNS IN TRANSLATION WORKS DONE BY TRANSLATORS IN SURAKARTA. - UTOMO, RISQI JATI (2007)
The type of the research is descriptive qualitative study especially about a case study, the method of collecting data are interview, observation, and documentation. The objectives of this research are to classify the class shifts of nouns and to describe the equivalence and non equivalence of the translation in translation works done by translators in Surakarta. The documents are the five translations texts. Each text consists of 7 sentences, 165 data belong to translation shifts and 35 data belong to equivalence and non equivalence sentence. Also, the writer finds the equivalence sentences and non equivalence sentence in translation.Here the writer just takes five translators in Surakarta randomly to obtain the data about the translators in Surakarta. The writer concludes that the educational background and experience of the translator can influence their result. The first translator has translated 7 sentences in the text; the writer finds 7 sentences or 100% which belong to non equivalence in translation. The second translator translate 7 sentences in the text, consist of 6 equivalence sentences or 85, 7 % belong to equivalence sentence, and 1 sentence or 14, 28% from data that belongs to non equivalence sentence in translation. The third translator has translated 7 data, containing of 4 sentences or 57, 14% and 3 sentences or 42, 9% which belong to non equivalence in translation. The forth translator translates 7 sentences in the text the writer finds 0 sentence or 100% which belongs to non equivalence in translation. The forth translator translates 7 sentences and finds 7 sentences or 100% which belong to non equivalence in translation. The fifth translator has translated 7 sentences in the text, the writer does not find equivalence sentence or 100% belongs to non equivalence sentence. Finally, it can be said that the message of linguistic units translation of the translators in Surakarta and its vicinity are not equivalent to the source language yet.